Efficacy and safety of the neoadjuvant chemoimmunotherapy with pembrolizumab plus docetaxel and cisplatin in resectable locally advanced squamous cell carcinoma of the head and neck - Wang, Jing; Zhang, Wenqian; Huang, Dongning; Liu, Zhu; Zhang, Wei; Li, Zhendong (Frontiers in Immunology, 2025)
BackgroundHead and neck squamous cell carcinoma (HNSCC) is the most common type of tumor originating from the squamous epithelium of the oral cavity, oropharynx, larynx and hypopharynx. There is an urgent need to enhance therapeutic efficacy and ensure the function preservation of HNSCC treatment. This study aimed to evaluate the efficacy and safety of neoadjuvant chemoimmunotherapy with pembrolizumab plus docetaxel and cisplatin in patients with resectable locally advanced HNSCC.MethodsThis was a prospective single-center, single-arm, open-label, phase II study involving patients with locally advanced HNSCC who were treated with pembrolizumab (200 mg) plus docetaxel (50 mg/m2) and cisplatin (50 mg/m2). After two cycles of the neoadjuvant chemoimmunotherapy, patients either proceeded to surgery or refused surgery and continued with chemoimmunotherapy and/or chemoradiotherapy. The primary endpoint was the objective response rate (ORR), while the second endpoints were primary lesion complete pathologic response (pCR), progression-free survival (PFS) rate, overall survival (OS) rate and safety.ResultsOverall, 52 patients with HNSCC were enrolled (45 males/7 females), with a median age of 61 years. The ORR rate was 87.8% (95% confidence interval [CI]: 75.2–95.4). Of the 27 patients who underwent resection, 12 (44.4%, 95% CI: 25.5–64.7) achieved a pCR and 15 (55.6%, 95% CI: 35.3–74.5) achieved an MPR. For the overall population, the PFS rates were 89.8% (95% CI: 77.2–95.6), 87.5% (95% CI: 74.2–94.2), and 72.7% (95% CI: 50.6–86.1), and the OS rates were 95.9% (95% CI: 84.7–99.0), 93.6% (95% CI: 81.5–97.9) and 84.9% (65.0–93.9), at 6 months, 12-months and 18 months, respectively. The most common adverse events were nausea/vomiting (12.2%), fatigue (10.2%), rash (8.2%), neurotoxicity (8.2%) and aminotransferases elevation (8.2%). Grades 3 and 4 adverse events occurred in 12 (24.5%) and 2 (4.1%) patients, respectively.ConclusionsPembrolizumab plus docetaxel and cisplatin reveals encouraging survival benefit with a manageable safety profile in patients with HNSCC.